Incongruence of gender, leadership roles and underrepresentation of women in sport leadership positions - Aman, Mirian Pabatao (2019)
The overall purpose of the study was to investigate the underrepresentation of women in top leadership positions of sport organizations through the perspectives and experiences of women leaders who have broken the barriers in sport leadership. To attain this purpose, the study employed five research questions purposely designed to answer the perceived barriers women leaders faced; their experiences related to the discriminatory practices in the organizations; influences of those prejudice; strategies they employed to overcome those barriers; and the support they provided to aspiring women leaders. The study employed phenomenological qualitative design where data were collected through face-to-face, semi structured interviews, observations and document analysis involving women leaders currently occupying top leadership positions in the national sport organizations. Framed by three theoretical perspectives of role congruity, homologous reproduction and pipeline problem, the current study sought to give voices to seven purposely selected women leaders who have navigated the male dominated environment of sport. The perspectives and experiences of the participants provided greater understanding of the underrepresentation of women in top positions of sport leadership. The data collected from three data sources elucidated five emerging themes: perceived barriers, experiences, influences of prejudice, strategies to overcome barriers and support. The participants perceived that the underrepresentation of women in top leadership positions is attributed to the perceived barriers women faced which include personal limitations where self-limiting behaviors and work-life conflict prompted it; sociocultural factors consist of traditional and cultural practices and society’s perceptions; and organizational factors consist of all-men’s network, gender discrimination and conflict among women. The participants also talked about their experiences related to the discrepancy of gender and leadership roles, organizational discrimination and pipeline problem. The participants revealed that gender stereotyping is evident through designation of leadership positions and gender role expectation; organizational prejudice is also occurring attributed to treatment and access discrimination manipulated by the majority in the organization; and candidate pool problem is apparent in the organization attributed to the lack of programs provided for the aspiring and potential women leaders, and low self-efficacy of women to come forward in the sport leadership pipeline. The participants also discussed the influences of prejudice in the organization, whereby the lack of leadership role models, lack of support and gender role conflict were identified. However, all the participants were hopeful of a better change and greater opportunities for women in sport leadership. They recommended strategies to overcome those barriers included networking, mentoring and developing self-efficacy. The participants also offered support which they believed will alleviate women’s underrepresentation in sport leadership, such as the needs for leadership role model and mentors, developmental programs and to work toward amending the selection process of selecting women leaders. All throughout this study, the findings showed that women were underrepresented in top leadership positions. The study revealed that there are many gendered barriers and prejudices that have discouraged women from pursuing leadership positions particularly at the top level. Significant findings of the study showed that the three theoretical perspectives employed are intertwining and collectively explained the underrepresentation of women in sport leadership.